2014
DOI: 10.7314/apjcp.2014.15.19.8367
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Caveolin-1 Expression in Gastric Cancer: a Meta-analysis

Abstract: The relationship between caveolin-1 (Cav-1) and clinicopathological characteristics of gastric cancer is controversial, although Cav-1 plays an important role in tumor metastasis. To evaluate the clinicopathological and prognostic value of expression in patients with gastric cancer, a meta-analysis was performed to investigate the impact on clinicopathological parameters and prognosis in gastric cancer cases. Studies assessing these parameters for Cav-1 in gastric cancer were identified up to June 2014. Finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…In addition, Yang et al reported that increased Cav-1 expression was associated with prolonged overall survival rate in hepatocellular carcinoma ( P = 0.021) [113]. Similar findings were also confirmed on breast cancer [99] and gastric cancer patients [114]. In particular, our analysis also revealed a close link between Cav-1 and lung cancer.…”
Section: Emerging Role Of Cav-1 In Cancer Preventionsupporting
confidence: 87%
“…In addition, Yang et al reported that increased Cav-1 expression was associated with prolonged overall survival rate in hepatocellular carcinoma ( P = 0.021) [113]. Similar findings were also confirmed on breast cancer [99] and gastric cancer patients [114]. In particular, our analysis also revealed a close link between Cav-1 and lung cancer.…”
Section: Emerging Role Of Cav-1 In Cancer Preventionsupporting
confidence: 87%
“…It has also been directly linked to the metastatic potential of pancreatic cancer cells through the regulation of epithelial to mesenchymal transition (EMT), a phenomenon closely related to the metastatic potential and chemoresistance of cancer cells (15,16). Nevertheless, conflicting results have been presented (17), with the loss of Cav-1 in the tumor stroma being associated with an adverse clinical outcome in a variety of cancer types (18-23).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that the loss of CAV1 in the tumor stroma results in an activated tumor microenvironment and was significantly related to metastasis, early tumor recurrence, and poor clinical outcome in breast cancer, prostate cancer, and other solid tumors 32 , 38 41 . Simultaneously, high CAV1 expression could predict a better overall survival in gastric cancer in a meta-analysis 42 .…”
Section: Resultsmentioning
confidence: 97%